Learning from the lived experiences of graduate student writers - Madden, Shannon; Eodice, Michele, 1957-; Edwards, Kirsten T.; Lockett, Alexandria, 1983- (University Press of Colorado e-book collection., 2020)
"A resource for understanding and resolving issues graduate students face. Offering diverse approaches, this book bridges the gap between theory and practice through structured examination of graduate students' narratives about their development as writers, as well as researched approaches for enabling these students to cultivate their craft"--